Indonesia's Ascent
XXIV, 372 p.
Keywords: This volume explores the domestic and transnational considerations associated with Indonesia's ascent, referring to its rise in terms of hard and soft power and its likely trajectory in the future. The range of contributors analyse economic resources, religious harmony, security, regional relations, leadership and foreign policy.